2013
DOI: 10.1089/ten.tea.2013.0229
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Potential of Stem Cells Derived from Periodontal Ligament or Gingival Tissue Sources Encapsulated in RGD-Modified Alginate Scaffold

Abstract: Mesenchymal stem cells (MSCs) provide an advantageous alternative therapeutic option for bone regeneration in comparison to current treatment modalities. However, delivering MSCs to the defect site while maintaining a high MSC survival rate is still a critical challenge in MSC-mediated bone regeneration. Here, we tested the bone regeneration capacity of periodontal ligament stem cells (PDLSCs) and gingival mesenchymal stem cells (GMSCs) encapsulated in a novel RGD-(arginine-glycine-aspartic acid tripeptide) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 51 publications
(75 reference statements)
6
131
0
1
Order By: Relevance
“…There is increasing interest in mesenchymal stem cells provide as they are an advantageous alternative therapeutic option for tissue regeneration in comparison to current treatment modalities (17). Previous reports showed that stem cells derived from the gingiva exhibited colony-forming abilities, plastic adherence and multilineage differentiation (osteogenic, adipogenic, chondrogenic) potency, and expressed CD44, CD73, CD90 and CD105 (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in mesenchymal stem cells provide as they are an advantageous alternative therapeutic option for tissue regeneration in comparison to current treatment modalities (17). Previous reports showed that stem cells derived from the gingiva exhibited colony-forming abilities, plastic adherence and multilineage differentiation (osteogenic, adipogenic, chondrogenic) potency, and expressed CD44, CD73, CD90 and CD105 (18).…”
Section: Discussionmentioning
confidence: 99%
“…GMSCs showed few inflammation-related changes when incubated with proinflammatory mediators (TNF-α, IL-1β), which suggested good response to unfavorable environmental conditions [10]. A bone regenerative capacity of GMSCs has been confirmed by multiple studies, as these cells were able to repair the critical size mandibular/calvarial defects in animals [11][12][13]. Moreover, the transplanted GMSCs proved a significant periodontal regenerative potential in vivo, with newly formed alveolar bone, cementum, and periodontal ligament fibers [14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, PDLSC microencapsulation in RGD-coupled alginate enhanced MSC viability, proliferation and osteogenic differentiation both in vitro and in vivo [41] . The combination of PDLSC with MSC demonstrated greater reossification when placed in a mouse calvarial defect model [41] .…”
Section: Pre-clinical Studiesmentioning
confidence: 90%